Integrating Inclusive Early Warning Technologies and Social Participation for Flood Resilience in Urban Communities - Anggun Puspitasari; Arin Fithriana; Taqwa Putra Budi Purnomo; Rezvia Sharla Azzahra; Jeremy Putra Pratama (Universitas Serang Raya, 2026)
Flooding in urban communities unintentionally reduces resilience, as seen in the partner area of RT 13 Pondok Betung, South Tangerang. Flooding disrupts residents' activities, impacting the economy, health, and environment. This community service activity aimed to raise awareness of the importance of early warning and inclusive community participation in flood disaster management. The activities were implemented in three stages: preparation, implementation, and evaluation, which involved the team and partners. The implementation activities focused on education on disaster mitigation, the implementation of inclusive early warning technology and a flood information system, and community capacity building through the formation of a Disaster Resilience Task Force. The program integrates early warning technology and social participation through the implementation of the Flood Information System (SIBAR). This demonstrates significant effectiveness in enhancing community-level disaster preparedness capacity. Evaluation findings through discussions and questionnaires indicated an increase in community awareness and response to flood risks following the intervention. Prior to SIBAR’s implementation, residents largely relied on informal information. Following the introduction of the inclusive early warning system, 83.3% of the respondents reported receiving real-time warnings via digital messages. Awareness of evacuation routes and emergency response procedures increased by 98%, indicating a significant shift from traditional alert patterns to technology-based preparedness. SIBAR also successfully expanded inclusivity by engaging women and senior citizens who were previously less involved in disaster management discussions, thus strengthening social cohesion by 91,6%. Adapting technology accessible to users with varying levels of digital literacy through the use of color-coding and simple text messaging contributed to a 100% user understanding rate. In addition to showcasing the principles of appropriate technology that is affordable, adaptive, and based on community ownership, this model has also proven viable for replication in other urban areas as a sustainable solution.